Eosinophilic gastroenteritis – a manifestation of an allergic disease in the gastrointestinal tract? Part 2. Treatment - Kuźmiński, Andrzej; Rosada, Tomasz; Przybyszewska, Justyna; Ukleja-Sokołowska, Natalia; Bartuzi, Zbigniew (Gastroenterology Review/Przegląd Gastroenterologiczny, 2023)
Treatment of eosinophilic gastroenteritis (EGE) is mainly empirical and is based on the assessment of symptom severity and the experience of clinicians. Patients with mild disease can be treated symptomatically, while patients with more severe symptoms or malabsorption symptoms require more aggressive therapy. So far, several therapeutic options have been proposed, including the following: dietary treatment, glucocorticosteroids, inhibitors of leukotriene receptors, mast cell stabilizers, immunomodulating drugs, and biological drugs. Unfortunately, there is still a lack of well-designed, prospective. and randomized clinical trials involving large groups of patients with EGE and assessing the effectiveness of individual treatments. More research is needed to compare the efficacy and safety profiles of the various treatments available, and to select the prognostic factors of relapse, which in turn will be extremely important in making decisions about the initial treatment phase and maintenance therapy.